1989
DOI: 10.1128/aac.33.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of norfloxacin on theophylline metabolism

Abstract: The purpose of this study was to investigate the effect of norfloxacin on theophyiline elimination. Ten normal volunteers were studied. In a randomized crossover sequence, each subject received 6 mg of aminophyiline per kg of body weight by a 30-min intravenous infusion on day 4 of taking norfloxacin (400 mg every 12 h) or while drug free. Mean theophylline clearance decreased and mean elimination half-life increased after norfloxacin administration (from 0.036 ± 0.006 to 0.033 + 0.004 liter/h per kg and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 15 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…It is interesting that this patient received two courses of norfloxacin without developing any clinically significant increase in theophylline levels. This is supportive of most studies of norfloxacin administration to healthy volunteers receiving aminophylline or theophylline, 7–10 although one study found an average decrease in theophylline clearance of 14.9%, 11 and Prince et al showed a decline in clearance of up to 31% compared to placebo among volunteers receiving an aminophylline infusion 12 . Three cases have been reported to the Food and Drug Administration suggestive of theophylline toxicity in patients taking norfloxacin 13 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It is interesting that this patient received two courses of norfloxacin without developing any clinically significant increase in theophylline levels. This is supportive of most studies of norfloxacin administration to healthy volunteers receiving aminophylline or theophylline, 7–10 although one study found an average decrease in theophylline clearance of 14.9%, 11 and Prince et al showed a decline in clearance of up to 31% compared to placebo among volunteers receiving an aminophylline infusion 12 . Three cases have been reported to the Food and Drug Administration suggestive of theophylline toxicity in patients taking norfloxacin 13 .…”
Section: Discussionsupporting
confidence: 60%
“…In patients with COPD, theophylline is commonly used to prevent bronchospasm, improve respiratory muscle function, and relieve dyspnea 6 . Several studies have examined the effect of quinolone administration on theophylline metabolism 4,5,7–15 . Raoof and colleagues administered ciprofloxacin at a dose of 750 mg twice daily to 33 hospitalized patients receiving theophylline.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been suggested to date to explain the influence that fluoroquinolones have on the pharmacokinetics of theophylline. Wijnands et al theorized that the 4-oxo-metabolite of fluoroquinolones such as enoxacin, ciprofloxacin, and pefloxacin acts as the inhibitor responsible for the interaction (33,34); however, good evidence against this supposition has recently been published (2,4,6).…”
Section: Resultsmentioning
confidence: 99%
“…perfusion over 30 min with a model 300 XL syringe-driver (Bard Medical Inc., Mississauga, Ontario, Canada). Blood samples were obtained at 0, 0.5, 1, 2, 3, 4,6,8,12,16,24, and 36 h, and urine was collected over the following intervals: 0, 0 to 2, 2 to 4, 4 to 8, 8 to 16, 16 to 24, and 24 to 36 h. Time-zero collection of urine allowed complete bladder emptying and a blank urine sample for analysis. Urine volume and pH were measured and recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, these agents are labeled for this interaction. The inhibitory effects were minor for norfloxacin (5,9,35,36) and neg-ligible or absent for ofloxacin (12,17,35,36,45), fleroxacin (38,40), lomefloxacin (32,46), temafloxacin (25,28,41), and sparfloxacin (21, 26) (for reviews on drug interactions between quinolones and methylxanthines, see references 13 and 43). The mechanism of this interaction is competitive inhibition of the enzyme mediating the main fraction of primary caffeine and theophylline metabolism (16), i.e., the cytochrome P-450 isoform CYP1A2 (15,18,49).…”
mentioning
confidence: 99%